Stress and its sequelae: An active inference account of the etiological pathway from allostatic overload to depression. (April 2022) - Arnaldo, Irene; Corcoran, Andrew W.; Friston, Karl J.; Ramstead, Maxwell J.D.
Abstract: Survival requires the implementation of adaptive changes that demand energy resources. The efficient regulation of energetic resources thus plays a critical role in enabling systems to adapt to the demands of their internal and external environments. The framework of active inference explains how living organisms can build probabilistic models that enable them to predict, track, and regulate energy expenditure in the short and long run. The aim of the paper is to characterize the physiological changes that accompany stress, and the relationship between these changes and the loss of confidence in a system's predictions about its internal and external milieu—ultimately manifesting as depressive symptomatology. We identify the systems that underwrite goal-directed behavior, and the neuroendocrine and immunological systems, as the hierarchical controller that regulates energy resources. In doing so, we establish an etiological pathway from allostatic overload to depression via active inference. Highlights: Adaptive changes that occur in response to stress have a severe impact in the predictive machinery. Alterations in hormonal and humoral states underwrite motivational and emotional disorders such as depression. Under active-inference allostatic load markers are embodied correlates of uncertainty.